An approach of power loss measurement for converter station and its key equipment - ZHENG Xin; YANG Jianhua; WEI Wei; MA Binqi; LI Shisong; ZHAO Wei (Diance yu yibiao)
At present, the commonly used power loss calculation method for converter station is mainly based on an analysis and calculation method which needs a large number of system operation and equipment performance parameters, so it is cumbersome and complicated to implement. In view of this, from the analysis and clarification of the key equipment of the converter station faults, explosions and fires and other physical mechanisms to provide reliable power loss monitoring data support, this paper puts forward an approach of power loss measurement for converter station and its key equipment. By equipping electrical energy metering devices with power monitoring function at the input and output ports of the converter station and the monitoring points of the key equipment inside the converter station and ensuring the time synchronisation to obtain the measurement results. Then, based on the principle of "power loss equals to the input power minus the output power", the power loss of the converter station and its key equipment could be measured. Based on the uncertainty assessment of the power loss measurement results of the converter station and its key equipment, a complete power loss monitoring system for the converter station is constructed.